2017
DOI: 10.1007/s10557-017-6725-2
|View full text |Cite
|
Sign up to set email alerts
|

SGLT-2 Inhibition with Dapagliflozin Reduces the Activation of the Nlrp3/ASC Inflammasome and Attenuates the Development of Diabetic Cardiomyopathy in Mice with Type 2 Diabetes. Further Augmentation of the Effects with Saxagliptin, a DPP4 Inhibitor

Abstract: Dapa attenuated the activation of the inflammasome, fibrosis, and deterioration of LVEF in BTBR mice. The anti-inflammatory, anti-fibrotic effects are likely SGLT2- and glucose-lowering-independent, as they were replicated in the in vitro model. The effects on remodeling were augmented when Saxa was added to Dapa. Yet, adding Saxa to Dapa did not result in a greater effect on myocardial fibrosis and collagen levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
220
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(236 citation statements)
references
References 48 publications
11
220
2
3
Order By: Relevance
“…Clearly, many of these findings are preliminary, proposing multiple exciting hypotheses and needs further investigation. In agreement with the present study, numerous in vivo studies using different rodent models of diabetes have demonstrated the beneficial effect of SGLT-2 inhibition on adverse cardiac remodeling and ventricular function [813]. However, most of the previous studies were descriptive in nature and do not provide mechanistic insight of empagliflozin mediated cardiac benefits (table 1).…”
supporting
confidence: 89%
“…Clearly, many of these findings are preliminary, proposing multiple exciting hypotheses and needs further investigation. In agreement with the present study, numerous in vivo studies using different rodent models of diabetes have demonstrated the beneficial effect of SGLT-2 inhibition on adverse cardiac remodeling and ventricular function [813]. However, most of the previous studies were descriptive in nature and do not provide mechanistic insight of empagliflozin mediated cardiac benefits (table 1).…”
supporting
confidence: 89%
“…These mechanisms are likely to be complementary, rather than mutually exclusive, all converging on one primary target, that is, IL‐1β, a major cytokine with a recognized role in the development of atherosclerosis and CV disease (Figure ). Finally, a glycaemia‐independent, molecule‐intrinsic, anti‐inflammatory mechanism has been proposed for canagliflozin and dapagliflozin, as has been shown in vitro in vascular endothelial cells and cardiofibroblast …”
Section: Evidence Of the Anti‐inflammatory Effect Of Sglt2 Inhibitorsmentioning
confidence: 99%
“…The heart failure phenotype in these trials was not investigated, but since patients with diabetes are prone to development of HFpEF, these drugs may have primarily acted to reduce the risk of HFpEF. It is therefore noteworthy that SGLT2 inhibitors reduce the accumulation and inflammation of epicardial fat, which may explain why this class of drugs appears to decrease myocardial fibrosis and improve ventricular diastolic filling dynamics, both experimentally and clinically . This anti‐inflammatory effect may be far more relevant to patients with HFpEF than those with HFrEF .…”
Section: Implications For Anti‐inflammatory and Antidiabetic Drugsmentioning
confidence: 99%